2015
DOI: 10.1177/1091581815599335
|View full text |Cite
|
Sign up to set email alerts
|

Determination of CYP3A4 Inducing Properties of Compounds Using a Laboratory-Developed Cell-Based Assay

Abstract: A cell-based assay to measure cytochrome P450 3A4 (CYP3A4) induction was developed to screen for potential CYP3A4 inducers. This 96-well format assay utilizes HepG2 cells transfected with a gene construct of CYP3A4 proximal promoter linked to green fluorescence protein (GFP) gene, and the expression of the GFP is then measured quantitatively. Bergamottin at 5 to 25 µmol/L produced low induction relative to the positive control. Both curcumin and lycopene were not found to affect the expression of GFP, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Although lycopene has been shown to upregulate the expression of CYP3A4, a major catabolic enzyme for docetaxel, 39,40 our PK analyses did not show any detrimental drug–drug interaction for the lycopene and docetaxel combination regimen. Instead, we observed that geometric mean docetaxel exposure (AUC inf ) increased by 9.5% and peak concentration ( C max ) increased by 15.1% with co‐administration of lycopene and docetaxel.…”
Section: Discussionmentioning
confidence: 60%
“…Although lycopene has been shown to upregulate the expression of CYP3A4, a major catabolic enzyme for docetaxel, 39,40 our PK analyses did not show any detrimental drug–drug interaction for the lycopene and docetaxel combination regimen. Instead, we observed that geometric mean docetaxel exposure (AUC inf ) increased by 9.5% and peak concentration ( C max ) increased by 15.1% with co‐administration of lycopene and docetaxel.…”
Section: Discussionmentioning
confidence: 60%
“…However, reports of reporter assay directly targeted hepatic CYP3A4 in herbal supplements are limited. It was reported that resveratrol induced the CYP3A4 transcriptional activity in HepG2 cells transfected with a GFP reporter vector (inserted CYP3A4 gene region, −1108 to +54 bp), although CYP3A4 inducers (Dex, omeprazole and Rif) did not upregulate the response dose dependently (Seah et al., 2015). Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of reporter assay directly targeted hepatic CYP3A4 in herbal supplements are limited. It was reported that resveratrol induced the CYP3A4 transcriptional activity in HepG2 cells transfected with a GFP reporter vector (inserted CYP3A4 gene region, −1108 to +54 bp), although CYP3A4 inducers (Dex, omeprazole and Rif) did not upregulate the response dose dependently (Seah et al, 2015). Kim et al (2004) reported that Rif did not induce CYP3A4 transcriptional activity in HepG2 cells transfected with a pCYP3A4-Luc vector (inserted CYP3A4 gene region, −863 to +64 bp), whereas the cells transfected with the vector and steroid and xenobiotic receptor vectors responded to Rif treatment similar to our results.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other in vitro investigations of CYP isoforms have revealed the inhibitory effects of curcumin and other curcuminoids [ 127 184 , 186 , 187 , 190 , 192 , 198 , 199 ]. Several additional studies utilizing intestinal human colon cancer cell lines, human hepatocytes, and HepG2 cells likewise failed to find any significant effects of curcumin on the mRNA expression of CYP3A4 [ 181 , 200 202 ]. The CYP3A4 isoform is the most notable CYP in that it is the primary drug-metabolizing enzyme in liver and intestinal tissue, catalysing the metabolism of half of all commercially available pharmaceuticals [ 203 205 ].…”
Section: Introductionmentioning
confidence: 99%